(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
Due to accelerated economic growth and increased food production, per capita rate of waste generation is also increasing in Bangladesh. Being the ninth most populous and twelfth most densely populated country in the world, Bangladesh will face serious crisis in both food scarcity as well as food loss if food wastage problem is not addressed. At household level, 5.5 percent food is wasted on daily basis. Due to its large volume, the disposal of food waste will be a major problem. Production of Organic acid from kitchen waste via anaerobic digestion can eliminate both waste pollution problem and high cost production of organic acid. Such organic acid can be used in food and beverages, cosmetics, and detergent industries. The present study was undertaken to convert kitchen waste generated from cafeteria of Atomic Energy Research Establishment (AERE), Savar, Dhaka into lactic acid using natural microflora. The number of indigenous microflora in kitchen waste were found to be 1.25×107 cfu/mL and pH range of 5.0-6.0. The ratio of rice, meat and vegetables in the kitchen waste was found to be 3:1:1. Kitchen waste was found to contain approximately 19.03% protein, 3.2% fat and 1.5% ash. Anaerobic digestion was carried out in shake flasks at various initial pH (5.0, 6.0 and 7.0) and different temperature (30℃, 37℃ and 45℃) for 96 hours. Highest lactic acid from Kitchen waste was produced (24.00 g/L) at 24 h at initially adjusted pH-7.0. An attempt to recover Lactic acid from fermented broth was conducted using rotary evaporation at 100℃ and at (60-65) cm. Hg vac. The results indicated that, the volume of food waste can be greatly reduced and can be converted into value-added products such as lactic acid via anaerobic fermentation. Asian Australas. J. Biosci. Biotechnol. 2020, 5 (3), 88-99